2020
DOI: 10.1111/psyg.12513
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep, care burden, and related factors among family caregivers at home

Abstract: Aim Several studies have reported a negative correlation between depressive symptoms and family caregivers' (FCs) subjective sleep status. However, there is a paucity of information on the association between objective/subjective sleep status, care burden, and related factors. Methods Participants were 23 pairs of care receivers (CRs; Mage = 82.7 ± 8.5 years; 69.6% women) receiving long‐term care at home and their FCs (Mage = 66.9 ± 11.0 years; 69.6% women). At baseline, demographic data, subjective sleep stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…14 Overall, ZCBS, WHO-5, and WEMWBS instruments have been extensively applied to determine caregiver's physical, mental, and psychological burden and well-being. [14][15][16] Moreover, they have all been adopted to study caregiver burden in Chinese caregivers. 17,18 All questionnaires were filled in privately by each caregiver.…”
Section: Methodsmentioning
confidence: 99%
“…14 Overall, ZCBS, WHO-5, and WEMWBS instruments have been extensively applied to determine caregiver's physical, mental, and psychological burden and well-being. [14][15][16] Moreover, they have all been adopted to study caregiver burden in Chinese caregivers. 17,18 All questionnaires were filled in privately by each caregiver.…”
Section: Methodsmentioning
confidence: 99%
“…This finding might indicate that the low SE of AD patients can lead to insomnia of their caregivers, thus increasing the caregiver burden. Ryuno et al [40] have reported that increased caregiver burden is associated with higher PSQI score (r = 0.62) and less TST measured by actigraph (r = -0.42) of caregivers.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 14 In most cases, older adults present difficulties in their daily living, requiring third-party care, such as family members or other caregivers, 15 greater attention and frequency of health resources, and a greater need of institutional resources, like nursing homes, for older adults. 8 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…6,12 Specifically, the presence of sleep disorders and their relation to different diseases or alterations in the health of older adults can have a significant impact on their occupational performance, 1 such as in the development of daily routines or their participation in society. 1,14 In most cases, older adults present difficulties in their daily living, requiring third-party care, such as family members or other caregivers, 15 greater attention and frequency of health resources, and a greater need of institutional resources, like nursing homes, for older adults. 8,15 Nursing homes tend to be the most frequented and required resources for the older population in need of some sort of assistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation